Onsite production of medical air: is purity a problem? - Edwards, Paul; Therriault, Patricia-Ann; Katz, Ira (Multidisciplinary Respiratory Medicine, 2019)
Introduction: Medical air (MA) is widely used in hospitals, often manufactured onsite by compressing external ambient air and supplied through a local network piping system. Onsite production gives rise to a risk of impurities that are governed by the same pharmacopoeia purity standards applicable to commercially produced MA. The question to be addressed in this paper is how to assess if a lack of purity poses a medical problem? Methods: The MA produced onsite at a major Canadian hospital was monitored for carbon dioxide (CO2) and other impurity gases at high frequency (one per minute) over a two-month period. Results: The average CO2 concentration was 255 ppm. The United States Pharmacopeia (USP) threshold of 500 ppm was exceeded during 1% of the total study period, and the average while exceeding the threshold was 526 ppm. The maximum concentration was 634 ppm. Discussion and conclusion: To our knowledge, there is only one study that evaluated the effects suffered by respiratory patients of elevated nitric oxide in MA; thus, it is not clear what are the medical bases for the thresholds stated in the USP. To perform a Quality Risk Assessment, the threshold and the time above threshold should be considered in determining the frequency of sampling and analysis, and operating methods required to ensure the quality of MA entering the pipeline meets the clinical, regulatory, and patient safety standards. In conclusion, because the USP does not provide impurity thresholds for specific patients nor time above thresholds, there is a need for the medical community to determine these quantities before it can be known if the purity of MA is a problem.